Safety assessment of sulfasalazine: a pharmacovigilance study based on FAERS database - Ye, Wangyu; Ding, Yuan; Li, Meng; Tian, Zhihua; Wang, Shaoli; Liu, Zhen (Frontiers in Pharmacology, 2024)
Background:Sulfasalazine is a widely used anti-inflammatory medication for treating autoimmune disorders such as ulcerative colitis(UC), Crohn's disease, and rheumatoid arthritis. However, its safety profile has not been systematically evaluated in real-world settings. By analyzing the FDA Adverse Event Reporting System (FAERS) database, we identified risk signals associated with adverse reactions to sulfasalazine, offering valuable insights for clinical decision-making and risk management.Methods:Reports of adverse events (AEs) associated with sulfasalazine, covering the period from Q1 2004 to Q4 2023, were extracted from the FAERS database. Detailed case information was aggregated to assess demographic characteristics. The associations between sulfasalazine and adverse events were evaluated using the Proportional Reporting Ratio (PRR), Reporting Odds Ratio (ROR), Bayesian Confidence Propagation Neural Network (BCPNN), and Empirical Bayes Geometric Mean (EBGM).Results:We extracted 7,156 adverse event reports from the FAERS database where sulfasalazine was identified as the "Primary Suspect (PS)" drug. Using disproportionality analysis, we identified 101 preferred terms (PT) related to sulfasalazine across 24 organ systems. Notable adverse reactions consistent with the drug's labeling were observed, including Stevens-Johnson syndrome, agranulocytosis, eosinophilic pneumonia, and crystalluria. Additionally, novel positive signals not previously documented in the drug label were identified, including acute febrile neutrophilic dermatosis, aseptic meningitis, glomerulonephritis, and hepatosplenic T-cell lymphoma.Most of the adverse reaction findings in this study are consistent with previous clinical research, and we have also identified new potential AEs associated with sulfasalazine.These findings provide valuable insights for the safety monitoring and clinical application of sulfasalazine.